Scientific activity of students as an important factor of sustainable development in the scientific and social spheres - Rebenok Valeria; Pronenko Evgeny (E3S Web of Conferences, 2023)
For sustainable development in various fields, highly qualified personnel are required. One of the ways to train such personnel is to involve young people in scientific activities while studying at the university. The author asks questions: how do students of psychological specialties perceive scientific activities, what emotional states arise in students when thinking about scientific activities or directly in the process of doing it. The introduction contains researches devoted to students' research activities; author presents his own model. The section "Methods" describes the sample: 73 students of psychological specialties; the author's questionnaire is given. The section "Results" reveals the students' opinion on how scientific activity can be included in various types of student activity, students' perception of scientific activity and their emotional states when thinking about it. The most frequently chosen emotional states are: interest and inspiration. The section "Discussion " contains the results obtained by other researchers. The author offers practical steps to popularize scientific activity at the university and introduce students to it. In conclusion, it is concluded that some university students have a superficial knowledge of research activities. Some students who would potentially like to start doing research don’t do it.